Novel two-dimensional semiconductor SnP3: high stability, tunable bandgaps and high carrier mobility explored using first-principles calculations. Issue 25 (7th June 2018) - Sun, Songsong; Meng, Fanchen; Wang, Hongyan; Wang, Hui; Ni, Yuxiang
Abstract : A novel semiconducting 2D material based on monolayer and bilayer SnP3 is proposed using first-principles calculations. Abstract : We propose a novel two-dimensional crystal based on layered bulk metallic SnP3 using first-principles calculations. The obtained low cleavage energy of monolayer and bilayer SnP3 implies the possibility of their exfoliation from layered bulk SnP3 experimentally. Monolayer and bilayer SnP3 are structurally stable with 0.72 eV and 1.02 eV indirect band gaps, respectively, at the HSE06 functional level. Tunable bandgaps can be achieved by strain engineering. With a compressive strain of 4%, the valence band maximum of bilayer SnP3 varies from the high symmetry point K to point Γ, resulting in transformation from an indirect to a direct semiconductor. Analogous to phosphorene, remarkably high carrier mobilities are predicted for monolayer SnP3, which is several times higher than that of monolayer GeP3 . The hole mobilities of bilayer SnP3 can reach as high as 10 4 cm 2 V −1 s −1 . Moreover, an excellent absorption coefficient in the range of solar spectrum was predicted. These results qualify monolayer and bilayer SnP3 as promising novel 2D materials for applications in microelectronics, optoelectronics and field-effect transistors.